Women and Investment: Analyzing Women’s Digital Existence in the Investment World through Simone de Beauvoir’s Perspective - Hidayati, Niswatin Nurul (Buana Gender: Jurnal Studi Gender dan Anak, 2025)
This research aimed to examine women’s existence in the digital space, focusing specifically on female content creators and audiences as active investors. This research was carried out on social media platforms, YouTube and Telegram, particularly within the Bibit Telegram community. The research highlighted that women possess both knowledge and skills in financial literacy, especially in the area of investments. Simone de Beauvoir’s existentialist feminism was employed as the theoretical framework to explore this phenomenon. A qualitative approach using netnography was adopted to investigate cultural and social interactions within digital spaces. The findings revealed that women's digital presence revolves not around physical appearance but around investment activities. This demonstrates their capability to plan for their financial futures, take on decision- making roles, and effectively manage investment funds. In a broader sense, the research connects this phenomenon to gender equality in finance and the advancement of women’s financial literacy.